(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Commensality and Religious Freedom. Commensality – the act of sharing a meal together – develops inter-human relations, cements sociability, merges the public with the private and is a manifestation of social solidarity. Liturgical acts: Lord’s Supper, Baptism, Religious Wedding, followed by common meals in which the guests share food together, strengthen and develop moral, ethical and social values. Commensality is the basis of human need for relationship, kindness, integrity, loyalty. Religious liberty – our first freedom – is essential for the entire network of international human rights protection, which serves as a citadel against authoritarianism and violations of individual or collective religious freedoms.